Effect of an mHealth intervention on physical activity outcomes among young adult cancer survivors: The IMPACT randomized controlled trial. Issue 3 (29th November 2022) - Valle, Carmina G.; Diamond, Molly A.; Heiling, Hillary M.; Deal, Allison M.; Hales, Derek P.; Nezami, Brooke T.; Pinto, Bernardine M.; LaRose, Jessica Gokee; Rini, Christine M.; Tate, Deborah F.
Abstract: Background: Physical inactivity is common in young adult cancer survivors (YACS), but evidence regarding effects of physical activity (PA) interventions among YACS is limited. The IMproving Physical Activity after Cancer Treatment (IMPACT) trial evaluated a theory‐based mobile PA intervention on total PA minutes/week (primary) and secondary outcomes (moderate‐to‐vigorous PA [MVPA], light PA, steps, sedentary behaviors) at 6 months in YACS. Methods: YACS ( N  = 280) were randomized to an intervention group or self‐help group. All participants received digital tools (activity tracker, smart scale, access to arm‐specific Facebook group) and an individual video chat session. Intervention participants also received a 6‐month program with behavioral lessons, adaptive goal‐setting, tailored feedback, tailored text messages, and Facebook prompts. PA was assessed via accelerometry and questionnaires at baseline and 6 months. Generalized estimating equation analyses tested between‐group differences in changes over time. Results: Of 280 YACS, 251 (90%) completed the 6‐month accelerometry measures. Accelerometer‐measured total PA minutes/week changed from 1974.26 at baseline to 2024.34 at 6 months in the intervention (mean change, 55.14 [95% CI, −40.91 to 151.19]) and from 1814.93 to 1877.68 in the self‐help group (40.94 [95% CI, −62.14 to 144.02]; between‐group p  = .84). Increases in MVPA were +24.67 minutes/week (95% CI, 14.77–34.57) in the intervention versus +11.41 minutes/week in the self‐help (95% CI, 1.44–21.38; between‐group p =  .07). Conclusion: Although the intervention did not result in significant differences in total PA, the increase in MVPA relative to the self‐help group might be associated with important health benefits. Future research should examine moderators to identify for whom, and under what conditions, the intervention might be effective. ClinicalTrials.gov Identifier: NCT03569605. Plain Language Summary: Physical inactivity is common in young adult cancer survivors. However, few interventions have focused on helping young adult cancer survivors to get more physical activity. The IMproving Physical Activity after Cancer Treatment trial compared a mobile health physical activity intervention with a self‐help group on total amount of physical activity at 6 months in a nationwide sample of young adult cancer survivors. Intervention participants did not improve their total amount of physical activity, but they did increase their moderate‐to‐vigorous intensity physical activity by twice as much as the self‐help participants. This increase in activity may be associated with health benefits. Abstract : Young adult cancer survivors participating in a mobile health intervention did not significantly increase accelerometer‐measured total physical activity after 6 months and did not differ from self‐help participants who only received digital tools (activity tracker, smart scale, access to a Facebook group). However, the intervention doubled the increase in accelerometer‐measured moderate‐to‐vigorous physical activity relative to the self‐help group, which may be associated with important health benefits.